Microsoft® Excel® 2016 bible - Walkenbach, John (John Wiley & Sons, Inc., 2016)
The complete guide to Excel 2016, from Mr. Spreadsheet himself. Whether you are just starting out or an Excel novice, the Excel 2016 Bible is your comprehensive, go-to guide for all your Excel 2016 needs. Whether you use Excel at work or at home, you will be guided through the powerful new features and capabilities by expert author and Excel Guru John Walkenbach to take full advantage of what the updated version offers. Learn to incorporate templates, implement formulas, create pivot tables, analyze data, and much more. Navigate this powerful tool for business, home management, technical work, and much more with the only resource you need, Excel 2016 Bible. * Create functional spreadsheets that work * Master formulas, formatting, pivot tables, and more * Get acquainted with Excel 2016's new features and tools * Customize downloadable templates and worksheets Whether you need a walkthrough tutorial or an easy-to-navigate desk reference, the Excel 2016 Bible has you covered with complete coverage and clear expert guidance.